178k views
5 votes
Expand (2x-3y+3)^2

PLEASE HELP!!

User Eria
by
5.4k points

2 Answers

2 votes

Answer:

4x² + 9y² + 12x - 18y - 12xy + 9

Explanation:

Given

(2x - 3y + 3)² = (2x - 3y + 3)(2x - 3y + 3)

Each term in the second factor is multiplied by each term in the first factor, that is

2x(2x - 3y + 3) - 3y(2x - 3y + 3) + 3(2x - 3y + 3)

Distribute the 3 parenthesis

= 4x² - 6xy + 6x - 6xy + 9y² - 9y + 6x - 9y + 9 ← collect like terms

= 4x² + 9y² + 12x - 18y - 12xy + 9

User Elyce
by
5.2k points
5 votes

Answer:

Explanation:

(x+ y + z)² = x² +y² + z² + 2xy +2yz + 2zx

Here, x = 2x ; y = -3y & z = 3

(2x - 3y + 3)² = (2x)² + (-3y)² + 3² + 2(2x)(-3y) + 2(-3y)3 + 2*3*(2x)

= 4x² + 9y² + 9 - 12xy - 18y + 12x

User Iwein
by
5.2k points